Safety of steroids in severe community-acquired pneumonia - Piedepalumbo, Federica Viola; Motos, Ana; Blasi, Francesco; Torres, Antoni (European respiratory review, 2025)
The systemic use of corticosteroids for patients with severe community-acquired pneumonia (sCAP) remains controversial in clinical practice, particularly in terms of the safety profile of these drugs. This narrative review aims to analyse the available literature data concerning the safety of short-term steroid use in the treatment of sCAP, while also highlighting potential future research directions. Several trials and meta-analyses have evaluated corticosteroid therapy as an adjuvant treatment for sCAP, yielding heterogeneous results regarding its efficacy and safety. Despite the wide variability in results, it is generally accepted that steroids are not associated with a significant risk of healthcare-associated infections, gastrointestinal bleeding or acute kidney injury in patients with sCAP in the short term. Nevertheless, such drugs are linked to hyperglycaemia, necessitating regular monitoring and appropriate management. The influence of steroids on long-term outcomes and their potential risks in viral sCAP still needs to be investigated.